THE EFFECT OF INSTRUCTIONAL MEDIA POWER POINT -BASED AND EMOTIONAL INTELLIGENCE ON DESCRIPTIVE WRITING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS CLASS VII SMPN 8 MUARO JAMBI - Puspayanti Puspayanti; Saharudin Saharudin; Budiyono Herman (Universitas Jambi, 2016)
This research aims to determine the effect of the use of instructional media power point-based and emotional intelligence on descriptive writing skill of Junior High School students number eight Muaro Jambi class seven. This is quantitative with quasi-experimental study which was conducted in two classes, class VII D as the experimental class (has treatment) and class VII F as a control class (has no treatment). Overall results of the research showed that there is no effect of the use of instructional media power point-based and emotional intelligence on descriptive writing skill of Junior High School students class seven at 95% level of significant. This is because of three hypotheses proposed; only one hypothesis stated that H1 received. The rest, hypothesis two and three H0 received. The results of hypotheses testing to hypotheses one, two, and three, are: (1) There is an effect of instructional media power point-based on descriptive writing skill of Junior High School students, (2) There is no effect of emotional intelligence on descriptive writing skill of Junior High School students, (3) There is no interaction between instructional media power point-based and emotional intelligence. It is true that the result of hypothesis testing on hypothesis one that there is an effect of instructional media power point-based, but the effect is not significant.Keywords: instructional media, power point -based, emotional intelegence, descriptive writing ability